2016
DOI: 10.1186/s13756-016-0120-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of transmission among healthcare workers in contact with a case of Middle East respiratory syndrome coronavirus infection in Thailand

Abstract: IntroductionA hospital-associated outbreak of Middle East Respiratory Syndrome Coronavirus (MERS-CoV) was reported. We aimed to assess the effectiveness of infection control measures among healthcare workers (HCWs) who were exposed to a MERS patient and/or his body fluids in our institute.MethodsA descriptive study was conducted among HCWs who worked with a MERS patient in Bamrasnaradura Infectious Diseases Institute, Thailand, between 18 June and 3 July 2015. Contacts were defined as HCWs who worked in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Compliance with hand hygiene can be significantly higher in an outbreak situation but is likely to remain an obstacle especially among physicians [16e18]. Transmission in healthcare settings can be successfully prevented when appropriate measures are consistently performed [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with hand hygiene can be significantly higher in an outbreak situation but is likely to remain an obstacle especially among physicians [16e18]. Transmission in healthcare settings can be successfully prevented when appropriate measures are consistently performed [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…This is in sharp contrast with the recent report from South Korea were none of 82 contacts of asymptomatic patients turned out to be positive. 33 Therefore, of those positive, only 43% had high-risk exposure. The relationship between the Ct value and transmission dynamics was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging to note that all healthcare workers who worked in a room with patients infected with MERS, or with the patients' bodily fluids in one small study, who were fully compliant with all protective wear including eye protection, showed no serum evidence of MERS-CoV antibodies. 24 At this time of limited information, we will need to stay highly vigilant to recognise early manifestation of COVID-19 including consideration of viral conjunctivitis as a possible presentation. Healthcare professionals should take the full recommended measures including strict hand hygiene and protecting the exposed mucous membranes, including wearing goggles or face masks.…”
mentioning
confidence: 99%